Elastic properties measurement of human enamel based on resonant ultrasound spectroscopy. (January 2019) - Niu, Haijun; Fan, Fan; Wang, Rui; Zhang, Qiang; Shen, Fei; Ren, Pengling; Liu, Tao; Fan, Yubo; Laugier, Pascal
Abstract: Objectives: To investigate the elastic properties of human enamel using resonant ultrasound spectroscopy (RUS). Methods: Six rectangular parallelepiped specimens were prepared from six human third molars. For all specimens, the theoretical resonant frequencies were calculated using the Rayleigh-Ritz method, knowing the specimen mass density and dimensions, and using a priori stiffness constants. The experimental resonant frequencies were measured and extracted by RUS. Then, the optimal stiffness constants were retrieved by adjustment of the theoretical resonant frequencies to the measured ones based on the Levenberg-Marquardt method. The engineering elastic moduli, including Young's moduli, shear moduli, and Poisson's ratios, were also calculated based on the optimal stiffness constants. Results: The five independent stiffness constants C 11, C 12, C 13, C 33, and C 44 were 90.2 ± 6.65 GPa, 34.7 ± 6.90 GPa, 29.5 ± 4.82 GPa, 83.5 ± 8.93 GPa, and 37.0 ± 10.9 GPa, respectively. Young's moduli E 11 and E 33, shear moduli G 13 and G 12, and Poisson's ratios υ 12 and υ 13 were 71.7 ± 7.34 GPa, 69.2 ± 7.32 GPa, 37.0 ± 10.9 GPa, 28.1 ± 4.35 GPa, 0.303 ± 0.098, and 0.248 ± 0.060, respectively. Significance: Elastic properties are critical for developing dental materials and designing dental prostheses. The RUS method may provide more precise measurement of elastic properties of dental materials.